An Application of NGS for Molecular Investigations in Perrault Syndrome: Study of 14 Families and Review of the Literature. Issue 12 (7th October 2016) - Lerat, Justine; Jonard, Laurence; Loundon, Natalie; Christin‐Maitre, Sophie; Lacombe, Didier; Goizet, Cyril; Rouzier, Cécile; Van Maldergem, Lionel; Gherbi, Souad; Garabedian, Eréa‐Nöel; Bonnefont, Jean‐ Paul; Touraine, Philippe; et al.
Abstract : Perrault syndrome is a rare autosomal recessive condition characterized by deafness and gonadic dysgenesis. In the literature 98 cases have been reported and only 25 mutations in the five Perrault genes have been identified. Thanks to NGS, four novel mutations have been identified in four Perrault genes ( C10orf2, CLPP, HARS2 and LARS2 ). Molecular analysis confirmed the clinical diagnosis in 28.6% and some genotype‐phenotype correlations were established. ABSTRACT: Perrault syndrome (PS) is a rare autosomal recessive condition characterized by deafness and gonadic dysgenesis. Recently, mutations in five genes have been identified: C10orf2, CLPP, HARS2, HSD17B4, and LARS2 . Probands included are presented with sensorineural deafness associated with gonadic dysgenesis. DNA was sequenced using next‐generation sequencing (NGS) with a panel of 35 deafness genes including the five Perrault genes. Exonic variations known as pathogenic mutations or detected with <1% frequency in public databases were extracted and subjected to segregation analysis within each family. Both mutations and low coverage regions were analyzed by Sanger sequencing. Fourteen female index patients were included. The screening in four cases has been extended to four family members presenting with PS phenotype. For four unrelated patients (28.6%), causative mutations were identified: three homozygous mutations in C10orf2, CLPP, and HARS2, and one compound heterozygous mutation in LARS2 . Three additional heterozygous mutations in LARS2 and HSD17B4 were found in three independent familial cases. All these missense mutations were verified by Sanger sequencing. Familial segregation analyses confirmed the molecular diagnosis in all cases carrying biallelic mutations. Because of NGS, molecular analysis confirmed the clinical diagnosis of PS in 28.6% of our cohort and four novel mutations were found in four Perrault genes. For the unsolved cases, exome sequencing should be performed to search for a sixth unknown PS gene.